2013
DOI: 10.1590/s1676-06032013000200024
|View full text |Cite
|
Sign up to set email alerts
|

Bat flies (Diptera: Streblidae) ectoparasites of bats at an Atlantic Rainforest site in northeastern Brazil

Abstract: Bat flies were surveyed between March, 2007 and February, 2008, in the Carnijó Private Natural Heritage Reserve (08° 07' S and 35° 05' W), an area of Atlantic Rainforest in the municipality of Moreno, in the Brazilian state of Pernambuco. Bats were captured biweekly using mist nets set during six hours each night. The ectoparasites were collected with tweezers and/or a brush wet in ethanol and stored in 70% ethanol. The specimens are deposited in the zoological reference collection of the Federal University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
6
18
1
3
Order By: Relevance
“…Trichobius joblingi was the most common species in the present study, as it was at other sites in Pernambuco (Soares et al, 2013) and Brazil (Bertola et al, 2005;Eriksson et al, 2011). While T. joblingi was recorded in one other bat species, its overall abundance was related to that of C. perspicillata, which was not only by far the most abundant bat in the sample -which is typical of most sites in Brazil (Peracchi et al, 2011) -but also had more than a third of the individuals infested with parasites.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Trichobius joblingi was the most common species in the present study, as it was at other sites in Pernambuco (Soares et al, 2013) and Brazil (Bertola et al, 2005;Eriksson et al, 2011). While T. joblingi was recorded in one other bat species, its overall abundance was related to that of C. perspicillata, which was not only by far the most abundant bat in the sample -which is typical of most sites in Brazil (Peracchi et al, 2011) -but also had more than a third of the individuals infested with parasites.…”
Section: Discussionsupporting
confidence: 53%
“…The seven species recorded here represent 27% of the total ectoparasitic dipteran fauna known to occur in Pernambuco (Guimarães, 1938;Soares et al, 2013), and two of the species -Trichobius uniformis and Strebla wiedemanni -had not previously been registered in the state.…”
Section: Discussionmentioning
confidence: 78%
“…Despite being a common species on the lists of bat flies in the Atlantic Forest (AZEVEDO; BERTOLA et al, 2005;SOARES et al, 2013), it was not previously reported in the study by Almeida et al (2011) in the state of Rio de Janeiro, mainly due to not catching S. lilium, which is its primary host (WENZEL, 1976).…”
Section: Resultsmentioning
confidence: 96%
“…No Brasil, apesar de haver uma maior concentração de estudos com ectoparasitos de morcegos nas regiões sul e sudeste (Graciolli et al 2008), há um aumento recente no número de estudos em outras regiões, como o nordeste , Soares et al 2013) e o centro-oeste (Graciolli et al 2006, Eriksson et al 2011. O Distrito Federal, embora seja a menor unidade federativa, é a que apresenta o maior número de espécies de moscas ectoparasitas de morcegos registradas no Brasil (Graciolli et al 2008 (Ratter et al 1997).…”
Section: Introdução Geralunclassified
“…Apesar de haver uma concentração de estudos de ectoparasitos de morcegos principalmente nas regiões sul e sudeste do Brasil (Graciolli et al 2006), está ocorrendo um aumento recente de estudos em outras regiões, como nordeste , Soares et al 2013) e centro-oeste (Graciolli et al 2006, Eriksson et al 2011 (Bush et al 1997), pois é nessa escala em que a interação entre as espécis de moscas ocorre (Tello et al 2008). …”
Section: Introductionunclassified